Electrochemical Determination of 2, 4, 6-Trinitrotoluene by Linear Sweep Voltammetry Using a Gold Nanoparticle/Mesoporous Graphitic Carbon Nitride Modified Glassy Carbon Electrode. (13th September 2022) - Xi, Shan-Shan; Sun, Yun-Yun; Wang, Zhi-Wen; Liu, Yao; Liu, Hao; Chen, Xing
Abstract: A novel electrochemical sensor for 2, 4, 6-trinitrotoluene (TNT) was constructed using a glassy carbon electrode (GCE) modified with gold nanoparticles (AuNPs)/mesoporous graphitic carbon nitride(mpg-C3 N4 ) nanocomposite (hereafter designated by AuNPs/mpg-C3 N4 ). A facile method based on ultraviolet excitation was used to produce the AuNPs/mpg-C3 N4 nanocomposite. The new AuNPs/mpg-C3 N4 nanocomposite was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and ultraviolet-visible diffuse reflectance spectroscopy. The AuNPs were evenly distributed on the surface of mpg-C3 N4 . The AuNPs/mpg-C3 N4 modified GCE sensor shows high sensitivity (viz., 0.32 μA/μM) and a low TNT detection limit (42 ppb) by linear sweep voltammetry (LSV). The enhanced electrochemical performance of AuNPs/mpg-C3 N4 GCE is attributed to synergistic interactions between AuNPs and mpg-C3 N4 . The AuNPs/mpg-C3 N4 /GCE demonstrated good selectivity, stability, and reproducibility for TNT. The AuNPs/mpg-C3 N4 /GCE show a 100% ± 5% TNT recovery for natural water analysis. The results show the potential in AuNPs/mpg-C3 N4 /GCE sensor applications for the determination of TNT.